The problem of Islamic terrorism in Kenya in terms of regional Security in East Africa - Joanna Bar (Ksiegarnia Akademicka Publishing, 2021)
The purpose of this article is to present the issue of security in the region of East Africa, particularly in Kenya, in view of the development of the phenomenon of Islamic terrorism. In the last two years it killed more than 400 people in this country and the scale of organized attacks is still increasing. In April 2015 Islamic militants from the Somali group al‑Shabaab attacked Garissa University College in northeastern Kenya. This terrorist attack confirmed that Kenyan authorities are not able to control the 700‑kilometre border with Somalia and ensure the security of citizens and tourists visiting the country. The threat of the escalation of acts of terrorism and the spread of violence to other countries in the region are becoming a major challenge to the foreign policy of Kenya and other countries in the region. In this article the author intends to present Kenya’s current actions in the fight against terrorism in Somalia and to assess the involvement of the African Union (AU) and the East African Community (EAC)– in terms of ensuring the regional security and the involvement of players from the region outside (the USA in particular) –in the context of the fight against Islamic terrorism on a global scale. Therefore the aim of the article is to attempt to evaluate the real possibility of providing effective aid to Kenya in the fight against terrorism. Despite the limited access to sources, dealing with this difficult subject of research has been justified by the fact that the awareness of the threat of Islamic terrorism against Kenya becomes necessary for the understanding of different phenomena and processes essential for the security of East African countries, and also for the fight against terrorism worldwide.